Spatially resolved atlas of breast cancer uncovers intercellular machinery of venular niche governing lymphocyte extravasation - Xin Wang; Zhanyu Wang; Qijun Liao; Pei Yuan; Junpu Mei; Yin Zhang; Chao Wu; Xiyu Kang; Sufei Zheng; Chenxuan Yang; Jiaxiang Liu; Qingyao Shang; et al. (Nature Communications)
Abstract Breast cancers present intricate microenvironments comprising heterotypic cellular interactions, yet a comprehensive spatial map remained to be established. Here, we employed the DNA nanoball-based genome-wide in situ sequencing (Stereo-seq) to visualize the geospatial architecture of 30 primary breast tumors and metastatic lymph nodes across different molecular subtypes. This unprecedented high-resolution atlas unveils the fine structure of the tumor vasculature, highlighting heterogeneity in phenotype, spatial distribution, and intercellular communication within both endothelial and perivascular cells. In particular, venular smooth muscle cells are identified as the primary source of CCL21/CCL19 within the microenvironment. In collaboration with ACKR1-positive endothelial cells, they create a chemokine-rich venular niche to synergistically promote lymphocyte extravasation into tumors. High venule density predicts increased immune infiltration and improved clinical outcomes. This study provides a detailed spatial landscape of human breast cancer, offering key insights into the venular regulation of tumor immune infiltration.